Optic nerve disc mathematical parameterization and the statistical comparison with measurements - Tiešis, Vytautas; Treigys, Povilas (Lietuvos matematikos rinkinys, 2010)
The paper deals with the automatic measurement of the optic nerve disc diagnostic parameters from eye fundus digital images. The automation gives objective measurements, in contrast to measurements by physicians that have large variance. The disc shape has been detected by the use of mathematical morphological operations, of Canny’s edge detection, of geometric Hough’s transformation and of the approximation by the least square method. The statistical tests confirm that there is no significant difference between measurements performed by physicians and automatic measurements.